Arboreal flora in Jamari FLONA, Rondônia (Research, Society and Development, 2021)
The present work aimed to characterize the composition and structure of tree species in the Jamari National Forest (FLONA), Rondônia. This information is an important tool for planning and conservation in tropical forests. The study was carried out at the Forest Management Unit III, in 17 plots of 50 x 100 m (total 8.5 ha), where the vegetation was sampled with DBH ≥ 10.0 cm. The richness and floristic composition were verified using the Shannon diversity index (H ') and Pielou's equability (J), and the phytosociological parameters and stocks by DAP class. The floristic composition was represented by 151 species, distributed in 34 families. The most important botanical families were Fabaceae, Moraceae and Lecythidaceae. Species diversity is considered to be high and uniform (H '= 3.87; J = 0.77). The identification of forest species represented a problem in the forest inventory, and it is important to invest in research focused on this area. Protium robustum; Peltogynepaniculata; Pouteria torta, Tachigali spp., Eschweilera spp. and Inga spp. represent the highest percentage of importance value and stocks in the forest. The largest stock in tree density, basal area and volume is concentrated in trees with DBH below 50 cm. In general, the Jamari FLONA is configured as an important Conservation Unit for the state of Rondônia and Brazil, as it contains a considerable biodiversity of the Amazonian tree flora and of great ecological and commercial value.